Guidelines and Good Clinical Practice Recommendations for Contrast Enhanced Ultrasound (CEUS) in the Liver – Update 2012 - Claudon, M.; Dietrich, C. F.; Choi, B. I.; Cosgrove, D. O.; Kudo, M.; Nolsøe, C. P.; Piscaglia, F.; Wilson, S. R.; Barr, R. G.; Chammas, M. C.; Chaubal, N. G.; Chen, M.-H.; Clevert, D. A.; Correas, J. M.; Ding, H.; Forsberg, F.; Fowlkes, J. B.; Gibson, R. N.; Goldberg, B. B.; Lassau, N.; Leen, E. L. S.; Mattrey, R. F.; Moriyasu, F.; Solbiati, L.; Weskott, H.-P.; Xu, H.-X. (Ultraschall in der Medizin - European Journal of Ultrasound, 2013)
Initially, a set of guidelines for the use of ultrasound contrast agents was published in 2004 dealing only with liver applications. A second edition of the guidelines in 2008 reflected changes in the available contrast agents and updated the guidelines for the liver, as well as implementing some non-liver applications. Time has moved on, and the need for international guidelines on the use of CEUS in the liver has become apparent. The present document describes the third iteration of recommendations for the hepatic use of contrast enhanced ultrasound (CEUS) using contrast specific imaging techniques. This joint WFUMB-EFSUMB initiative has implicated experts from major leading ultrasound societies worldwide. These liver CEUS guidelines are simultaneously published in the official journals of both organizing federations (i.e., Ultrasound in Medicine and Biology for WFUMB and Ultraschall in der Medizin/European Journal of Ultrasound for EFSUMB). These guidelines and recommendations provide general advice on the use of all currently clinically available ultrasound contrast agents (UCA). They are intended to create standard protocols for the use and administration of UCA in liver applications on an international basis and improve the management of patients worldwide.
Keywords: diagnosis; metastases; hepatocellular carcinoma; focal nodular hyperplasia; hemangioma; microbubble